Economic modeling in the post great recession era incomplete data, imperfect markets - Silvia, John; Iqbal, Azhar (Economist); House, Sarah Watt 1985- (Wiley and SAS business series., 2017)
"Economic Modeling in the Post Great Recession Era presents a more realistic approach to modeling, using direct statistical applications to address the characteristics and trends central to current market behaviors. This book's unique focus on the reality of today's markets makes it an invaluable resource for students and practitioners seeking a comprehensive guide to more accurate forecasting. While most books treat the economy as if it were in a vacuum, building models around idealized or perception-biased behaviors, this book deals with the economy as it currently stands in a state of recovery, limited by financial constraints, imperfect information, and lags and disparities in price movements. The authors identify how these characteristics impact various markets' behaviors, and quantify those behaviors using SAS as the primary statistical tool."--Provided by publisher.